Efektivitas Penggunaan Aplikasi Quizizz sebagai Media Evaluasi Hasil Belajar Siswa - Khulud, Hanifah (TSAQOFAH, 2024)
Technological and communication advances have a significant impact on various sectors of life, especially in the world of education. The use of technology in learning aims to improve the quality of education. One form of technology utilization is through the use of the Quizizz application as a medium for evaluating student learning outcomes. Therefore, this article is written with the aim of describing the effectiveness of using quizizz as a medium for evaluating student learning outcomes. The method used in this article is the library study method (library research) which is based on literature from accredited national journals sinta two (2) to sinta six (6) for the last 5 years, obtained from Google Scholar.The results of the study obtained show that the use of the Quizizz application as a medium for evaluating student learning outcomes is very effective and suitable for use as a medium for evaluating student learning outcomes. Based on the results of the study that has been obtained by the author, we can know that the effectiveness of Quizizz as an evaluation media can be seen from the Quizizz features that make it easier for teachers and students to carry out the evaluation process. The use of Quizizz as an evaluation media is relatively cheap and practical when compared to using conventional paper-based methods. In addition, evaluation using Quizizz can encourage students to improve learning outcomes because students feel motivated when taking quizzes on the platform.